Orchids of Negeri Sembilan : Beyond Turner’s Catalogue - Mohd Akmal, Mohd Raffi; Farah Alia, Nordin; Rusea, Go; Wong, Wee Nee (Jabatan Perhutanan Negeri Sembilan, 2024)
An updated Orchidaceae species inventory from Negeri Sembilan was compiled from previous scientific expeditions throughout the state, as well as from a BRAHMS database of vandaceous orchids in Peninsular Malaysia. A total of 150 species from 75 genera were recorded. From the account, Vanilla montana is identified as new record to Negeri Sembilan. Based on the conservation status, two species were recognized as critically endangered, namely Gastrochilus calceolaris and Corybas holttumii, while Vanilla montana, Corybas carinatus and Neuwiedia zollingeri var. singapureana were categorized as endangered, vulnerable, and near threatened, respectively. In a nutshell, this inventory serves as the most updated documentation on the orchid species diversity from Negeri Sembilan. It is expected that more species are yet to be discovered and documented from this species-rich region of southern Peninsular Malaysia.